The Effect of Financial Development on Foreign Direct Investment in ASEAN+4 - Suci, Stannia Cahaya; Chendrawan, Tony Santika; Zahara, Vadilla Mutia (Universitas Pasundan, 2024)
Foreign direct investment (FDI) is an important input to the achievement of a country's goals such as economic growth and poverty. The study looks at the impact of financial development (FD) on foreign direct investment (FDI) in nine ASEAN member states along with China, India, Japan and South Korea in 2018-2022. The estimate method used is the GMM method (generalized method of moment). The study found that financial development positively and significantly influenced the flow of foreign direct investment. Trade openness, human development and price levels were also found to influence FDI while economic growth was found to have no significant impact. The findings in this study imply that a good financial system is essential to attract even higher FDI.